Various Software Development Life Cycle Models - Jindal, Sahil; Gulati, Puneet; Rohilla, Praveen (IJRDO -Journal of Computer Science Engineering, 2015)
An SDLC model is a conceptual framework describing different activities in a software development project from planning to maintenance. This process is associated with several models, each including a variety of tasks and activities. Software development is a cumbersome activity requiring proper identification of requirements, their implementation, and software deployment. However, the activities do not end there. After the distribution of the software, proper maintenance has to be provided in a timely manner. So to carry out the software development process efficiently we require certain models which help us to carry out our work properly